The Factors Influencing the Lack of Interest Among Mothers in Choosing Effective Implant Contraception at PMB Nur’aini Helvetia in 2024 - Isnaini, Puspita; Surbakti, Imran Saputra; Kamisah, Kamisah; rokayah, siti; bakara, sri muliana; Maulida, Maulida (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Determining new candidates for contraceptive users to choose the right prevention technique cannot be separated from individual behavioral factors. From the beginning, it is known that this may be the mother's impression of contraceptive use based on her understanding. Additionally, the benefits for the mother in using contraceptives also allow her to make a decision, even though the chosen contraceptive method may not be entirely appropriate. The purpose of this study is to identify the factors influencing the lack of interest among mothers in choosing contraceptive methods. This research is an analytical survey with a cross-sectional approach, analyzing the relationship between risk factors and effect factors. The study was conducted at PMB Nur’aini Helvetian, Medan, North Sumatra Province, from March to July 2024. The population in this study consisted of women of childbearing age who were contraceptive acceptors at PMB Nur-Aini Helvetia, totaling 102 people, using a purposive sampling technique. Based on the Slovin formula, a sample of 50 respondents was obtained. The data analysis used was the chi-square test. The research results showed with a p-value of 0.05 that there is a significant relationship between knowledge (p=0.018), attitude (p=0.014), husband's support (p=0.025), and PUS (Women of Childbearing Age) culture (p=0.025) with the selection of contraceptive methods among PUS. Conclusion: The selection of contraceptive methods among PUS at PMB Nur’aini Helvetia found that husband's support, knowledge, attitude, and culture are related to the choice of contraception.